(untitled)
By deducing the inequality of weight coefficient: ω 1pt 1pt (n) = _m = 0^∞ 11pt 1pt m + 1pt 1pt n +1 (21pt 1pt n + 121pt 1pt m + 1)^12 Â < π -56(2n + 1 + 34(2n + 1)^ - 1 ), where n N. We obtain on a strengthened of the more accurate Hilbert’s inequality., number=1, journal=European Journal of Pure and Applied Mathematics, year=2011, month=Jan., pages=83–88